REPRESENTASI MASKULINITAS DAN KESENJANGAN RAS DALAM IKLAN REXONA MEN X CHELSEA - Khairul Syafuddin (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2022)
Advertising is made to communicate a message from a product to consumers. This makes the advertising narratives formed according to social constructs that are close to the reality of consumers. One of the advertisements that represents the social condition of contemporary masculinity is Rexona Men x Chelsea: Keringat? Bau Badan?. Rexona tries to construct masculine men through grooming products for men. This in turn leads to the hybridization of masculinities. This hybrid masculinity is influenced by bodywork which is not only shown through the strength, hardness, and smell of sweat. But also the action in carrying out body care. The findings from the study show that the Rexona Men x Chelsea advertisement constructs this masculinity through a series of visuals shown by the selected brand ambassadors. There are three brand ambassadors, namely Callum, Marcos, and Pedro. The three of them are shown as masculine men through the training activities they are doing, the work they have which is represented through the uniforms they wear, to sweat and body odor. All these things are packaged in visual and written text. Furthermore, at the end of the commercial, hybrid masculinity is shown when Marcos does not sweat and smells due to wearing personal care products. This advertisement also shows a form of racism through a visual that is directed at Callum. This racism is shown in Callum's own eyes, Marcos's eyes to Callum, and gave Callum a mop. From the advertisements that offer body care products, it can be seen that there is a racial gap that is used as a spectacle to offer products for sale.